2016
DOI: 10.1111/adb.12477
|View full text |Cite
|
Sign up to set email alerts
|

CYP2A6 metabolism in the development of smoking behaviors in young adults

Abstract: Cytochrome P450 2A6 (CYP2A6) encodes the enzyme responsible for the majority of nicotine metabolism. Previous studies support that slow metabolizers smoke fewer cigarettes once nicotine dependent but provide conflicting results on the role of CYP2A6 in the development of dependence. By focusing on the critical period of young adulthood, this study examines the relationship of CYP2A6 variation and smoking milestones. A total of 1209 European American young adults enrolled in the Collaborative Study on the Genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…nicotine+cue self-administration behavior in our protocol relies on nicotine, the number of infusions earned over a 3hrs session was positively related to the cotinine (main nicotine metabolite) over nicotine ratio (FigS5f). Consistent with the literature (37,38) , this also supports that high nicotine intake is favored by a fast nicotine metabolism (high cotinine/nicotine ratio).…”
Section: Nicotine+cue Self-administrationsupporting
confidence: 90%
See 2 more Smart Citations
“…nicotine+cue self-administration behavior in our protocol relies on nicotine, the number of infusions earned over a 3hrs session was positively related to the cotinine (main nicotine metabolite) over nicotine ratio (FigS5f). Consistent with the literature (37,38) , this also supports that high nicotine intake is favored by a fast nicotine metabolism (high cotinine/nicotine ratio).…”
Section: Nicotine+cue Self-administrationsupporting
confidence: 90%
“…In the recent years, nicotine metabolism has focused interest as a phenotypic biomarker of smoking heaviness (37) and therapeutic response (81). Fast metabolizers being at risk for heavy smoking (37), and slow metabolizers benefitting from nicotine replacement therapies (NRT) and normal metabolizers from treatments like varenicline (81).…”
Section: Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in individuals with the inactive CYP2A6 genotype, the CYP2A6 enzyme might not affect metabolic activation of N-nitrosamines and subsequently reduce the risk of lung cancer. Second, CYP2A6 is a major enzyme responsible for nicotine metabolism 38 , where inactive CYP2A6 causes lower nicotine dependence and thus affects smoking behaviour [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Wassenaar et al 18 observed a higher quantity of cigarettes consumed per day by individuals possessing normal metabolizer genes in comparison with those having slow metabolizers. Although other studies have not reported the same association 74 or even divergent results 75,76 , several works have shown a direct association between the CYP2A6 genotype of lower enzyme activity and the lower risk of becoming a smoker, less nicotine dependence, fewer cigarettes consumed and greater success in cessation [17][18][19][20][21] .…”
Section: Polymorphism Of Cyp2a6mentioning
confidence: 98%